The QuinteT Recruitment Intervention supported five randomized trials to recruit to target: a mixed-methods evaluation - Rooshenas, L; Scott, L; Blazeby, J; Rogers, C; Tilling, K; Husbands, S; Conefrey, C; Mills, N; Stein, R; Metcalfe, C; Carr, A; Beard, D; et al. (Elsevier, 2018)
Objective To evaluate the impact of the QuinteT Recruitment Intervention (QRI) on recruitment in challenging randomized controlled trials (RCTs) that have applied the intervention. The QRI aims to understand recruitment difficulties and then implements “QRI actions” to address these as recruitment proceeds. Study Design and Setting A mixed-methods study, comprising (1) before-and-after comparisons of recruitment rates and the numbers of patients approached and (2) qualitative case studies, including documentary analysis and interviews with RCT investigators. Results Five UK-based publicly funded RCTs were included in the evaluation. All recruited to target. Randomized controlled trial 2 and RCT 5 both received up-front prerecruitment training before the intervention was applied. Randomized controlled trial 2 did not encounter recruitment issues and recruited above target from its outset. Recruitment difficulties, particularly communication issues, were identified and addressed through QRI actions in RCTs 1, 3, 4, and 5. Randomization rates significantly improved after QRI action in RCTs 1, 3, and 4. Quintet Recruitment Intervention actions addressed issues with approaching eligible patients in RCTs 3 and 5, which both saw significant increases in the number of patients approached. Trial investigators reported that the QRI had unearthed issues they had been unaware of and reportedly changed their practices after QRI action. Conclusion There is promising evidence to suggest that the QRI can support recruitment to difficult RCTs. This needs to be substantiated with future controlled evaluations.